Reviving Zakat for Micro-Financing and Socio-Economic Development in Algeria - Fatima Sayah; Khairunnisa Musari (Center of Strategic Studies (PUSKAS) BAZNAS, 2022)
Algeria has managed zakat for wealth distribution and project financing by managing and investing the zakat funds as microfinance to create jobs, reduce unemployment and poverty as well as contribute to financing the local development and encouraging investments by providing financial aids and good loan in financing micro-enterprises through qard el-hassan. Although the qard el-hassan program was freezed in 2014, qard el-hassan is slowly but surely has demonstrated its ability as an Islamic solution to achieve its social and economic goals in Algeria by managing the zakat fund as a financing source. By using descriptive statistics as analytical tool, this paper attends to describe: (1) Facts and figures of zakat in Algeria and (2) The role of zakat for financing through qard el-hassan and socio-economic development in Algeria. Overall, this paper encourages the government of Muslim countries to optimize the zakat fund as a financing source through qard el-hassan and/or another productive contract to face the socio-economic financing problem. Moreover, for the Government of Algeria, allocating zakat funds into qard el-hassan has to be considered to be revived to continue the impact of the Algerian zakat fund on the Algerian socio-economic development.